2019
DOI: 10.1021/acs.jcim.9b00572
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking as a Promising Predictive Model for Silver Nanoparticle-Mediated Inhibition of Cytochrome P450 Enzymes

Abstract: Cytochrome P450 (CYP) enzymes are responsible for oxidative metabolisms of a large number of xenobiotics. In this study, we investigated interactions of silver nanoparticles (AgNPs) and silver ions (Ag+) with six CYP isoforms, namely, CYP1A2, CYP2C9, CYP2C19, CYP2D6, CYP2E1, and CYP3A4, within CYP-specific inhibitor-binding pockets by molecular docking and quantum mechanical (QM) calculations. The docking results revealed that the Ag3 cluster, not Ag+, interacted with key amino acids of CYP2C9, CYP2C19, and CY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Molecular docking study showed that SSd displayed a high binding energy of −11.3 kcal/mol. It has been reported that the amino acid residues of Phe57, Phe108, Ile120, Leu211, Phe241, Ile301, Phe304, Ile369, Leu373, Arg105, Leu364, Arg365, Leu366, Phe367, Pro368, Ala370, Met371, Arg372 and Glu374 in CYP3A4 played a key role in ligand binding 38‐44 . Another study suggested that Phe57, Arg105, Arg106, Phe108, Phe215, Met371, Arg372, Leu373, Glu374 and Arg375 were involved in interaction between sauchinone and CYP3A4 protein 45 .…”
Section: Discussionmentioning
confidence: 98%
“…Molecular docking study showed that SSd displayed a high binding energy of −11.3 kcal/mol. It has been reported that the amino acid residues of Phe57, Phe108, Ile120, Leu211, Phe241, Ile301, Phe304, Ile369, Leu373, Arg105, Leu364, Arg365, Leu366, Phe367, Pro368, Ala370, Met371, Arg372 and Glu374 in CYP3A4 played a key role in ligand binding 38‐44 . Another study suggested that Phe57, Arg105, Arg106, Phe108, Phe215, Met371, Arg372, Leu373, Glu374 and Arg375 were involved in interaction between sauchinone and CYP3A4 protein 45 .…”
Section: Discussionmentioning
confidence: 98%
“…For instance, cytochrome P450 (CYP) is an important enzyme system for drug metabolism. Hence, molecular docking approaches can be applied to NP and CYP enzymes in order to estimate the molecular interactions of the proteinligand complex on the basis of its 3D structure [76]. Inhibition of the CYP enzyme by co-administered drugs is clinically significant in terms of drug−drug interactions, which may reduce drug efficacy or increase toxicity [77][78][79].…”
Section: Molecular Dockingmentioning
confidence: 99%
“…ChEBI (Chemical Entities of Biological Interest (https://www.ebi.ac.uk/chebi/) was used to obtain the 3-D structure of MgO-NPs with ChEBI ID 36973. Dock v.6.5 was used for docking [13][14][15] .…”
Section: In Silico Interaction Of Aspergillus Oryzae β-Galactosidase With Mgo-npsmentioning
confidence: 99%
“…2]. The proteinligand complex was obtained by Chimera v.1.6.2 14 and PyMOL v.1.3 15 for visual analyses. Ligplot v.1.4.5 program showed the ligand interaction plots of protein-ligand complexes.…”
Section: In Silico Studiesmentioning
confidence: 99%